VASEKTOMI DAN PEMOTONGAN TARING PADA MONYET EKOR PANJANG (Macaca fascicularis) DI KAWASAN WISATA PURA BATU PAGEH, DESA UNGASAN BADUNG - I Nengah Wandia; I Gede Soma; I Ketut Suatha; I GA. Arta Putra; Sri Kayati Widyastuti; Aida Louise Tenden Rompis (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2012)
Population growth and aggressiveness are important factors on macaque populations that their habitats are used as tourist destinations. Controlling those two factors may decrease the negative impact of the macaque population both to the environment and the internal circumstance of the population. This Community Service was packed as a vasectomy and canine cutting services on the adult male of long tailed macaques occupying a tourist destination of Pura Batu Pageh, Ungasan Village, Badung Regency. Vasectomy is a surgical division of all or part of vas deferens to induce sterility. Surgical resection of part of vas deferens used a midline slicing method. In this program, one selectively adult male was successfully vasectomized and the four canines were also cut successfully. Later inspection showed that there was no any problem with the individual that formerly subjected to medical treatments and even the wounds went to be healing completely.